“IMPASSE” OR “WORK IN PROGRESS”?: NOTES ON THE ACTUAL FEMINIST DEBATE IN ITALY - Re, Lucia (Gênero & Direito, 2015)
The essay illustrates some aspects of the more recent feminist debate in Italy, connecting it with the international debate and presenting the origin and design of this special issue of the Journal “Genero e direito”.